Multi-Technique Investigation of a Biomimetic Insect Tarsal Adhesive Fluid - Fowler, J. Elliott; Gorb, Stanislav; Baio, Joe E. (Frontiers in Mechanical Engineering, 2021)
There is substantial motivation to develop novel adhesives which take advantage of the superior adhesive strength and adaptability of many natural animal adhesives; however, the tools typically used to study these mechanisms are incapable of determining the precise interactions of molecules at an adhesive interface. In this study, a surface specific, order sensitive vibrational spectroscopy called sum frequency generation (SFG) is, for the first time, combined with multiple bulk characterization techniques to examine a novel, simple biomimetic adhesive fluid inspired by tarsal fluid of insects. Insects perform complex adhesive demands, including sticking, climbing vertically and running upside-down with little difficulty. Thus, we hypothesize that both bulk and surface specific properties of the fluid contribute to the success of this wet adhesive mechanism. SFG spectra of biomimetic emulsion exhibited similar hydrocarbon organization on hydrophobic and hydrophilic substrates to natural beetle fluid previously studied with the same method (Fowler et al., 2021). Bulk characterization techniques indicated that the emulsion had a shear-thinning profile with the ability to enhance traction forces during climbing and low surface tension ideal for surface wetting on the majority of natural surfaces. Multi-technique comparisons between emulsion and pure squalane revealed that a hydrocarbon only based fluid could not replicate the traction promoting properties of the emulsion. We conclude that the insect tarsal fluid adhesive mechanism relies upon contributions from both surface-specific properties optimizing traction force and bulk properties promoting rapid surface wetting and maintaining pull-off force for fast detachment.